Feminist theory and cultural studies : stories of unsettled relations / Sue Thornham. - Thornham, Sue (Cultural studies in practice, 2001)
This text explores the key methodological approaches and theoretical debates within feminist cultural studies. The book is aimed at students wishing to understand the contribution feminism has made to cultural studies.